Visible-light enabled C4-thiocyanation of pyrazoles by graphite-phase carbon nitride (g-C3N4). (3rd August 2021) - Pan, Junyi; Liu, Cheng; Wang, Jianqiang; Dai, Yunqiao; Wang, Shengyu; Guo, Cheng
Graphical abstract: Abstract: Thiocyanation is an important and effective way to form CS bonds in organic synthetic methodology. Especially, thiocyanation of pyrazole attracts the attention of many researchers because sulfur-containing compounds are widely applied in many crucial fields such as organic materials, agrochemistry, nanotechnology, etc. Herein, we described A rapid metal- and additive-free method for C(sp 2 )-H thiocyanation of pyrazoles under visible light at room temperature by using a sustainable catalyst of graphite-phase carbon nitride (g-C3 N4 ) and a thiocyanating agent of ammonium thiocyanate. The method presents many advantages, such as usage of eco-friendly photoredox catalyst, a wide range of substrates and a good yield of products, etc.